Semantic Web and social web heading towards living documents in the life sciences - García Castro, A.; Labarga, A; García, Leyla; Giraldo, O; Montana, C; Bateman, JA (Elsevier, 2010)
Rather than a document that is constantly being written as in the wiki approach, the Living Document (LD) is a document that also acts as a document router, operating by means of structured and organized social tagging and using existing ontologies. It offers an environment where users can manage papers and related information, share their knowledge with their peers and discover hidden associations amongst the shared knowledge. The LD builds upon both the Semantic Web, which values the integration of well-structured data, and the Social Web, which aims to facilitate interaction amongst people by means of user-generated content. In this vein, the LD is similar to a social networking system, with users as central nodes in the network, with the difference that interaction is focused on papers rather than people. Papers, with their ability to represent research interests, expertise, affiliations, and links to web based tools and databanks, are the central axis for interaction amongst users. To support this, we have also implemented a novelweb prototype that enables researchers to accomplish three activities central to the Semantic Web vision: organizing, sharing anddiscovering. Availability: http://www.scientifik.info/livingdocument.